Clinical evaluation of polypropylen plates of limited contact related to fractures from dog's appendicular skeleton (Veterinary Science, 2017)
This work is about the use of orthopedic implants like polypropylen bone plates of limited contact related mainly to fractures of long bones from dogs appendicular skeleton. Mechanical behavior and effect upon the callogenesis of fractures are also investigated. These bone plates were applied to 6 mature dogs (males and females) of mean height (between 10 and 20 Kg of weight) brought to the external consulting room of Small Animals (Faculty of Veterinary Sciences, UNLPam). The orthopedic implants were manufactured from polypropylen tubes (4 mm wall thickness) and all of them were made of he same width and length (2 cm x 15 cm) with six holes of 4 mm for fixing screws three in each fracture end. Notches were performed on the contact surface with the bone in order to let a minimum rubbing between plates and bones. As a conclusion, the plates of osteosynthesis made of polypropylen are motionless and do not produce adverse reactions that may influence on the patient's general condition, allowing an early limb's support. The formation of a periosteal callus of great size was observed
Keywords: Plates; Polypropylen; Limited contac